Contemporary issues of heat illnesses - Parker, J. (The Sport Journal, 2011)
Abstract Heat illnesses are of major concern. More and more high school, college, and professional athletes are suffering from and/or dying from heat related illnesses. With all of the knowledge that medical professionals have in this day-in-age, there should be fewer instances of heat illnesses. Parents, coaches, and athletes also need to be aware of prevention and treatment procedures in case an emergency occurs. Heat stroke, the most serious heat illness, is a life threatening emergency and needs to be treated immediately. Ice water immersion is the best method for lowering the body temperature quickly and effectively.